การพัฒนาระบบสารสนเทศสำหรับการจัดการรายละเอียดรายวิชา (มคอ.3) - เติมวิทย์ขจร, ไกรทพนธ์; หะยีวาเงาะ, นิมารูนี; นามบุรี, ศิริชัย (วารสารวิทยบริการ มหาวิทยาลัยสงขลานครินทร์ | Academic Services Journal, Prince of Songkla University; Vol 29 No 2 (2561): Academic Services Journal, Prince of Songkla UniversityDO - 10.14456/asj-psu.2018.26, 2018)
งานวิจัยนี้มีวัตถุประสงค์เพื่อออกแบบและพัฒนาระบบสารสนเทศสำหรับการจัดการรายละเอียดรายวิชา (มคอ.3) โดยผู้วิจัยได้ดำเนินการตามวงจรชีวิตการพัฒนาระบบ (SDLC) มีกระบวนการดังนี้ ระยะที่ 1 วางแผนโครงการ ระยะที่ 2 วิเคราะห์ระบบ ระยะที่ 3 ออกแบบระบบ ระยะที่ 4 นำไปใช้ ในการดำเนินการวิจัยผู้วิจัยกำหนดกลุ่มตัวอย่างจำนวน 2 กลุ่ม คือ 1) กลุ่มตัวอย่างในขั้นการพัฒนาระบบ ได้แก่ อาจารย์ผู้สอน ประธานหลักสูตร รองคณบดีฝ่ายวิชาการ รองอธิการบดีฝ่ายเทคโนโลยีสารสนเทศ ผู้อำนวยการสำนักประกันคุณภาพ เจ้าหน้าที่ฝ่ายจัดการศึกษา 2) กลุ่มตัวอย่างในขั้นการประเมินประสิทธิภาพและประสิทธิผล ได้แก่ ผู้ทรงคุณวุฒิด้านเทคโนโลยีสารสนเทศ อาจารย์ ผู้บริหาร ผลการวิจัยพบว่า ระบบสารสนเทศสำหรับการจัดการรายละเอียดรายวิชา (มคอ.3) ได้เชื่อมโยงข้อมูลจาก มคอ.2 ส่งผลให้รายวิชาที่ปรากฏในระบบสารสนเทศสำหรับการจัดการรายละเอียดรายวิชา (มคอ.3) ถูกต้องตามแผนการเรียน และ พบว่า ระบบสารสนเทศสำหรับการจัดการรายละเอียดรายวิชา (มคอ.3) มีประสิทธิภาพและประสิทธิผลในระดับดีมาก คำสำคัญ: การพัฒนาระบบสารสนเทศ, วงจรชีวิตการพัฒนาระบบ, การจัดการรายละเอียดรายวิชา, มคอ.3   This study aimed to design and develop the information system for Course Specification (TQF 3). The system development life circle (SDLC) concept, which consisted of four processes; project planning, system analysis, system design, and implementation, was applied in the study. The samples of the study were categorized to two groups. The first group was samples who were involved in system development level. They were lecturers, head the program, vice dean of academic affairs, vice president of information technology, director of quality assurance office, and educational management staff. The samples of the second group were IT specialists, lecturers, and administrators who participated in efficiency and sufficiency evaluation. The study revealed that the developed information technology system for Course Specification (TQF 3) was linked by TQF2. The information technology system for Course Specification (TQF 3) to be applicable for the courses whose lecturer were more than one. Lastly, the develop system was capable to be integrated with service unit database which made the information technology system for Course Specification (TQF 3) accordant with course syllabus. The study also revealed that the developed system for the information technology system for Course Specification (TQF 3) has sufficiency and efficiency at high level. Keywords: information system development, system development life cycle, subject content information system, TQF 3